Estudo de equilíbrio líquido-vapor de soluções hidroetanólicas contendo frutose - Dias, Rafael Macedo (2016)
Fructose (1,3,4,5,6-pentahydroxyhex-2-one) is an important sugar in global market because its unique characteristics when compared to another sugars. It becomes the fructose economically attractive besides the fact that it is not easily produced. Fructose may be produced by crystallization from its aqueous solution adding ethanol as antisolvent, and afterward a separation process will be necessary to separate ethanol+water+fructose to become the process practicable. Applying this way, ethanol may be recovered using a distillation column and vaporliquid equilibrium data for water+ethanol+fructose mixture are necessary but it is not available in literature yet. Thermodynamic models are necessary to modelate a distillation column. Thus, this work has the objective of obtain VLE of hydroethanolic solutions contain fructose, and estimate parameters of an adequated model to describe the behavior of the mixture. In this work, Vapor-liquid equilibrium (VLE) data for water+ethanol+fructose and water+ethanol were determined using a modified ebulliometer based on vapor recirculation operating at atmospheric pressure of São Carlos. The composition was determinated combinating measures of refractive index and mass balance. Curves of VLE with fix composition of fructose containing 10.3%, 20.7% and 31.0% in mass were determinated, besides a binary curve with water and ethanol to validate the method. The estimative of parameters was realized in Scilab software version 5.5.1, utilizing the Levenberg-Marquardt method. The experimental data were used to estimate parameters of models based on excess Gibbs energy and local composition (Wilson, NRTL, UNIQUAC, P&M-UNIQUAC). Among all the model tested on estimative of parameters, the best model to describe the experimental data was the P&M-UNIQUAC model whose parameters were considered dependents of temperature with maximum deviation of 6,10% to water in vapor phase. Were evaluated models based on modifications of UNIFAC model, in these cases using parameters of interaction available in literature, to these cases the best model to describe the experimental was the mS-UNIFAC with maximum deviation of 14,45% to water in vapor phase. The results show that is possible determinate VLE data contain fructose utilizing the methology adopted and that fructose influences in VLE.